ISOLASI DAN KARAKTERISASI BAKTERI PENGHASIL ANTIBIOTIK DARI TANAH SAWAH DI NAEN KABUPATEN TIMOR TENGAH UTARA - Lukas Pardosi; Adelya Irawan Manalu (Fakultas Pertanian, Universitas Timor, 2022)
Soil is a habitat for small animals and microorganisms. The most abundant microorganisms in soil are bacteria. The soil used in the study was soil obtained from paddy fields in Naen, North Central Timor Regency.The study aimed to characterize the bacterial isolates obtained from the paddy fields which are known to produce antibiotics. Rice soil samples were taken at a depth of about 15 cm from the soil surface and then cultured in Nutrient Agar media with graded dilutions. Characterization was carried out by macroscopic observation, namely direct observation, then a challenge test was carried out against S. aureus bacteria. The results showed that there were 6 bacterial isolates with macroscopic results mostly irregular in shape and 1 isolate fibrous. There were 4 bacterial isolates namely STS1, STS3, STS4, and STS6 which had inhibitory power against the growth of S. aureus.